2018
DOI: 10.5692/clinicalneurol.cn-001188
|View full text |Cite
|
Sign up to set email alerts
|

A case of multiple cerebral hemorrhage caused by sudden increase of eosinophil in a patient with eosinophilic granulomatosis with polyangiitis

Abstract: A 42-year-old woman with bronchial asthma was admitted to our hospital due to sensory dominant mononeuritis multiplex lasting for more than 6 months. At that time, her eosinophil count was 761/μl and her sural nerve biopsy showed no findings suggestive of vasculitis. Four months later, she experienced sudden convulsions and right hemiparesis due to left lobular parietal subcortical hemorrhage, when her eosinophil count was elevated to 3,257/μl. Numerous microbleeds and small infarctions were also detected in t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 12 publications
0
3
0
Order By: Relevance
“…In the largest review of the literature, André et al reported 46 cases of cerebral infarction, 9 cases of intracerebral hemorrhaging, and 12 cases of subarachnoid hemorrhaging among 88 cases of EGPA with central nervous system involvement between 1992 and 2014 ( 3 ). Yamada et al reported a case of EGPA with massive subcortical hemorrhaging in the parietal lobe accompanied by multiple lesions of subarachnoid hemorrhaging and small infarction colocalized in the border zone area ( 7 ). She additionally reviewed 7 cases of subcortical hemorrhaging with EGPA, although none of them presented with both cerebral infarction and subarachnoid hemorrhaging concomitantly ( 7 ).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In the largest review of the literature, André et al reported 46 cases of cerebral infarction, 9 cases of intracerebral hemorrhaging, and 12 cases of subarachnoid hemorrhaging among 88 cases of EGPA with central nervous system involvement between 1992 and 2014 ( 3 ). Yamada et al reported a case of EGPA with massive subcortical hemorrhaging in the parietal lobe accompanied by multiple lesions of subarachnoid hemorrhaging and small infarction colocalized in the border zone area ( 7 ). She additionally reviewed 7 cases of subcortical hemorrhaging with EGPA, although none of them presented with both cerebral infarction and subarachnoid hemorrhaging concomitantly ( 7 ).…”
Section: Discussionmentioning
confidence: 99%
“…Yamada et al reported a case of EGPA with massive subcortical hemorrhaging in the parietal lobe accompanied by multiple lesions of subarachnoid hemorrhaging and small infarction colocalized in the border zone area ( 7 ). She additionally reviewed 7 cases of subcortical hemorrhaging with EGPA, although none of them presented with both cerebral infarction and subarachnoid hemorrhaging concomitantly ( 7 ). The present case is the first to show that cerebral infarction can colocalize with subcortical hemorrhaging and subarachnoid hemorrhaging in the border zone area.…”
Section: Discussionmentioning
confidence: 99%
“…The frequency of stroke in PSV has been studied in relatively small and heterogeneous cohorts, most commonly retrospectively assessed over the whole disease course [10,[16][17][18][19][20][21][22][23][24][25]). Ischaemic stroke has been described as the most common subtype of stroke in these patients [16,22], but there are limited available data on the frequency of haemorrhagic stroke and cerebral venous thrombosis (CVT) in PSV [26][27][28][29][30], except for CVT in Behçet's disease [31].…”
Section: Introductionmentioning
confidence: 99%